Pengaruh Kepemilikan Institusional, Kepemlikan Manajerial, Dan Komite Audit Terhadap Integritas Laporan Keuangan - Angel Novelina Putri Tamara; Andi Kartika (Universitas Pendidikan Ganesha, 2021)
This study aims to analyze and examine the effect of institutional ownership, managerial ownership, and audit committee on the integrity of financial statements. The population used in this study is all manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) in the last five years, namely 2015-2019 as many as 779 companies. The sampling method used in this study is using a purposive sampling technique to obtain a sample of 150 companies. The data analysis method used in this research is multiple linear regression analysis. The results of this study explain that institutional ownership and managerial ownership have a significant positive effect on the integrity of financial statements, while the audit committee has no effect on the integrity of financial statements.